(untitled) (Hackensack, N.J., 2005)
Processing in magnetic fields is a rapidly expanding research area with a wide range of promising applications in materials science, development and design. Numerous research centers dedicated to materials research and processing in magnetic fields have been created around the world
Keywords: Magnetic fields,Magnetic fields,Từ trường; Industrial applications